Cognitive Ability and Perceived Disagreement in Learning - Piotr Evdokimov; Umberto Garfagnini (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Do agents believe to be agreeing more with others in the long-run? This paper designs an experiment to study how cognitive abilities affect actual and perceived disagreement in a standard sequential belief updating task with public signals. We document a persistent gap in the perception of disagreement as a function of cognitive ability. Higher cognitive ability is associated with less perceived disagreement, although the average subject underestimates the extent of actual disagreement regardless of cognitive ability. Learning about the state of the world has little effect on the evolution of perceived disagreement when controlling for cognitive ability. Providing subjects with information about their partner's cognitive ability affects perceived disagreement only when the partner is less cognitively able.
Keywords: C90; D83; D89; 330; cognitive ability; disagreement; learning